Plasma Urea Cycle Metabolites May Be Useful Biomarkers in Children With Eosinophilic Esophagitis - Moye, Lindsay M.; Liu, Yuying; Coarfa, Cristian; Putluri, Nagireddy; Rhoads, Jon Marc (Frontiers in Pediatrics, 2019)
Background: Eosinophilic esophagitis (EoE) is a disorder of the esophagus that has become increasingly recognized in children. Because these children undergo multiple endoscopies, discovering a noninvasive biomarker of disease activity is highly desirable. The aim of this study was to use targeted plasma metabolomics to identify potential biomarker candidates for EoE in a discovery phase. Methods: A prospective, single-center clinical trial was performed on 24 children ages 2-18 years with and without EoE undergoing upper endoscopy for any indication. Blood samples were collected for metabolomics profiling using the subclasses: amino acids, tricarboxylic acid cycle, acetylation and methylation. Using mass spectrometry and systematic bioinformatics analysis, 48 metabolites were measured and compared between children with active EoE (+EoE) and controls (–EoE). To investigate the effect of proton pump inhibitor (PPI) use on metabolites, patients were also stratified based on PPI use (+PPI, –PPI). Results: Seven children had active EoE at the time of endoscopy. Eleven children were on PPI (4 with EoE). Of the 48 metabolites measured, 8 plasma metabolites showed statistically significant differences (p <.05) comparing +EoE –PPI to –EoE –PPI, a few of which were upregulated metabolites involved in the urea cycle. There were 14 significant differences comparing +EoE +PPI to +EoE –PPI. This demonstrated that in EoE patients, PPI use upregulated metabolites involved in the urea cycle, while it downregulated metabolites involved in methylation. Comparison among all four groups, +EoE +PPI, +EoE –PPI, –EoE +PPI and –EoE –PPI, revealed 27 significantly different metabolites. +EoE +PPI had downregulated methionine and N-acetyl methionine, while both +EoE groups and –EoE +PPI had upregulated homocysteine, N-acetylputrescine, N-acetylornithine, arginine and ornithine. Conclusion: The present study revealed key plasma metabolite differences in children with EoE compared to unaffected controls. Notable candidate biomarkers include dimethylarginine, putrescine, and N-acetylputrescine. PPI use was shown to influence these urea cycle metabolites, regardless of EoE presence. Therefore, future studies should distinguish patients based on PPI use or determine metabolites while not on treatment. These findings will be confirmed in a larger validation phase, as this may represent a significant discovery in the search for a noninvasive biomarker for EoE.